Response of Red Chili (Capsicum anuuum L.) to Humic Acid Application in Dryland - Budiyati Ichwan; Mukhsin Mukhsin; Eliyanti Eliyanti; Windasari Windasari (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2022)
Red chili cultivation in dry land in an effort to increase production and productivity is constrained by the limited availability of water. The application of humic acid increases the ability of soils to retain restricted water and enhances plant growth and yield. This study aimed to investigate the response of red chili grown in dry land to the application of humic acid. Research place at the Teaching and Research Farm, Faculty of Agriculture, Jambi University. A Randomized Block Design with 5 replications was used in this study. The treated humic acid dose is 0 ton/ha, 2.5 ton/ha, 5 ton/ha, 7.5 ton/ha, and 10 ton/ha. Red chili gave a positive response to the application of humic acid by increasing plant height, number of branches, fruit number, and fruit weight. The dose of humic acid that gave the highest yield of 6.6 ton/ha was 5 ton/ha. This study was only able to provide a yield of 44.06% when compared to the potential yield of red chili.